Direct demonstration of electric chirality control in a helimagnetic YMn 6 Sn 6 by spin-polarized neutron scattering - Hidetoshi Masuda; Yutaro Yanagisawa; Kazuki Ohishi; Yusuke Nambu; Yoichi Nii; Yoshinori Onose (Proceedings of the National Academy of Sciences, 2026)
The spiral handedness of magnetic moments, referred to as chirality, gives rise to emergent electromagnetic phenomena in helimagnets. In insulating helimagnets, known as multiferroics, the cycloidal spin structure induces electric polarization by utilizing the inverse Dzyaloshinskii–Moriya mechanism. Spin-polarized neutron diffraction experiments, which directly probe circular spin arrangements, clearly demonstrated that an electric field controlled the chirality in multiferroic helimagnets. On the other hand, it was unclear until recently how the chirality could be controlled in metallic helimagnets where a large electric field cannot be applied, while the chirality control technique in metallic helimagnets should enable the exploration of chirality-dependent spintronic functionalities. Recently, Jiang et al. succeeded in controlling the chirality of a spiral structure by the simultaneous application of a magnetic field and electric current in a metallic helimagnet, utilizing the nonreciprocal electronic transport as an indirect probe of chirality, highlighting the need for a neutron diffraction experiment that directly probes the chirality. Here, we directly demonstrate the chirality control in a metallic helimagnet YMn 6 Sn 6 by means of spin-polarized neutron diffraction, which should give rise to a firm basis for the development of future helimagnetic spintronics.